2015
DOI: 10.1093/cid/civ163
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Among Afebrile and Vaccinated Healthcare Workers

Abstract: Nearly half of HCWs with influenza were afebrile prior to their diagnosis. HCWs with respiratory symptoms but no fever may pose a risk of influenza transmission to patients and coworkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
1
37
3
Order By: Relevance
“…The most frequent symptoms in HP with influenza were fever, chills and headache, which were present in more than 90% of cases, followed by myalgia, arthralgia and cough, with a frequency greater than 80%. In contrast, in a study of HP in Chicago in 2014, only 51% of the participants presented with fever as a symptom . In our population, approximately one‐fifth of those assessed reported diarrhoea as a symptom.…”
Section: Discussioncontrasting
confidence: 77%
“…The most frequent symptoms in HP with influenza were fever, chills and headache, which were present in more than 90% of cases, followed by myalgia, arthralgia and cough, with a frequency greater than 80%. In contrast, in a study of HP in Chicago in 2014, only 51% of the participants presented with fever as a symptom . In our population, approximately one‐fifth of those assessed reported diarrhoea as a symptom.…”
Section: Discussioncontrasting
confidence: 77%
“…The outbreak that we describe was short compared to other examples in the literature. [4][5][6]23 We suspect the early identification, removal of ill HCWs, and universal use of oseltamivir prophylaxis, as recommended by the CDC, helped to reduce secondary cases. 1,24 Nosocomial outbreaks of influenza have been shown to consume considerable amounts of hospital resources.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, as fevers were not consistently reliable for detecting influenza in HCWs, more specific guidance is needed to help form policy. 23 In addition to following the CDC guidance with regards to using fever resolution as a measure for returning to work, we also recommended any HCWs with ILI stay home until 24 hours after the peak of their respiratory symptoms. On return, we recommend wearing a surgical mask until the respiratory symptoms are completely resolved, as is standard.…”
Section: Discussionmentioning
confidence: 99%
“…Infected HCW have been shown not to refrain from work despite showing symptoms suggestive of influenza [1,15]. Intriguingly, a recent study demonstrated that afebrile and vaccinated HCW can introduce influenza into the hospital [16]. On the other hand, it is well documented that vaccination rates among HCW are insufficient to minimize the risk of nosocomial influenza in most acute care hospitals and mandatory vaccination against influenza is discussed [17].…”
Section: Discussionmentioning
confidence: 99%